A Study Comparing Immunohistochemistry, Fluorescence in situ hybridization, GeneXpert® Breast Cancer STRAT4 Assay for Determining Hormone Receptor, Human Epidermal Growth Factor Receptor 2, Ki67 Status in Invasive Breast Carcinoma in Moroccan women - Rajaa El Aje; Abdellah Naya; Ayoub Khoaja; Younes Zaid; Mounia Oudghiri; Jodi Weidler; Mehdi Karkouri (Progress in Microbes and Molecular Biology)
The accurate assessment of hormone receptors, HER2, and Ki-67 proliferative index provides meaningful information about breast cancer prognosis and prediction of therapy response. Immunohistochemistry, the most common method for evaluating these prognostic biomarkers, can be impacted by numerous variabilities due to pre-analytical/analytical factors and subjective interpretation by pathologists. The Xpert® Breast Cancer STRAT4, an RT-qPCR based system, can be used to classify invasive breast carcinomas based on the assessment of these four biomarkers; Methods: We evaluated ESR1, PGR, ERBB2, and MKi67 mRNA expression by Xpert Breast Cancer STRAT4 and ER, PR, HER2 and Ki67 by IHC (FISH for HER2 IHC 2+) in 200 formalin-fixed paraffin-embedded (FFPE) tissue blocks with invasive breast cancer, collected from the Pathology Department of Casablanca Ibn Rochd University Hospital; Results: Concordance between Xpert ® Breast Cancer STRAT4 and IHC was 93.5% for ER, 83.51% for PR, 95% for HER2 (92% for IHC+FISH), and 81.20% for Ki67 (excluding intermediate IHC Staining 10 ≤ %IHC <20). The simple Kappa coefficient was, for ER, 0.830 (P < 0.0001), 0.565 (P < 0.0001) for PR, 0.838 (P < 0.0001) for HER2-IHC, 0.771 (P < 0.0001) for HER2 IHC+FISH and, for, Ki67, 0.458 (P < 0.0001); Conclusions: We demonstrated globally a high concordance between centrally assessed IHC, IHC+FISH and mRNA measurements of ER/ESR1 and HER2/ERBB2, and a moderate agreement between PR/PGR and Ki67/MKi67. These findings provide an additional, objective, and quantitative assessment of tumor receptor status in breast cancer.